Intracavernosal OnabotulinumtoxinA Exerts a Synergistic Pro-Erectile Effect When Combined with Sildenafil in Spontaneously Hypertensive Rats. Issue 6 (29th March 2022) - Giuliano, Francois; Joussain, Charles; Denys, Pierre; Laurin, Miguel; Behr-Roussel, Delphine; Assaly, Rana
ABSTRACT: Background: Botulinum toxin A (BTX-A) has a variety of uses in medicine. Some evidence suggests that intracavernosal (ic) BTX-A injection administered in addition to phosphodiesterase type 5 inhibitors (PDE5-Is) could effectively treat erectile dysfunction (ED) in insufficient responders to PDE5-Is. Aim: To provide experimental pharmacological evidence for the use of onabotulinumtoxinA ic alone or in combination with PDE5-Is for difficult-to-treat ED. We thus compared the effects of BTX-A ic alone and BTX-A ic combined with PDE5-I iv, and a placebo treatment ic or iv. Methods: Erectile function was evaluated following cavernous nerve electrical stimulation (6 V, 1-millisecond pulse, 45-second duration) at different frequencies (0, 2, 3, 4, 5, 7.5, and 10 Hz) in 4 groups (n = 8 / group) of anesthetized, spontaneously hypertensive rats, a robust animal model of ED of vascular origin. Rats were treated by onabotulinumtoxinA 10U or saline ic 1 week prior to erectile function testing and sildenafil (0.3 mg/kg) or saline iv 4 minutes prior to testing. Frequency-response curves were compared with a 2 way ANOVA. Outcomes: Both onabotulinumtoxinA ic, and sildenafil iv significantly improved erectile responses in spontaneously hypertensive rats, however the effect was greatly amplified when the treatments were combined. Results: Intracavernosal pressure and/or mean arterial pressure ratios were significantly increased by sildenafil and onabotulinumtoxinA ic versus the control condition. OnabotulinumtoxinA 10U ic combined with sildenafil iv significantly potentiated erectile responses. Area under the curve and/or mean arterial pressure ratio increased by 19% with sildenafil iv, by 15% with onabotulinumtoxinA ic and by 58% with the combined treatment following cavernous nerve electrical stimulation at 6V, 1 ms, 10 Hz: these stimulation parameters elicited the maximal erectile response. Clinical Translation: These data provide a pharmacological rationale for the combined administration of onabotulinumtoxinA ic and sildenafil iv since the effects of both treatments were potentiated when their administration was combined. Strengths & Limitations: First evidence of a synergistic pro-erectile effect of BTX-A combined with PDE5-I, however the mechanism behind the pro-erectile effect of BTX-A ic remains hypothetical. Conclusions: These results support further studies into the mechanisms behind the pro-erectile effect of BTX-A ic, as well as multicenter randomized control trials to evaluate the safety and efficacy of BTX-A ic combined with sildenafil for difficult-to-treat ED.